On a Statistical Mechanics Approach to Some Problems of the Social Sciences - Contucci, Pierluigi; Vernia, Cecilia (Frontiers in Physics, 2020)
This work is a survey of some results on a statistical mechanics approach to the social sciences emerged in the last two decades. The pioneering work of Daniel McFadden, known as discrete choice theory, is interpreted in terms of a non-interacting model and extended along the lines of the Brock and Durlauf interacting systems. The generalization to the multi-populated model is presented and two specific case studies are reviewed with their phenomenological and theoretical analysis.